Distinct strains of the re-emergent Cassava common mosaic virus (genus: Potexvirus) infecting cassava in Argentina - Zanini, Andrea Alejandra (2018)
Cassava common mosaic disease (CCMD) has been reported in all regions where cassava is grown in the Americas and the causal agent, Cassava common mosaic virus (CsCMV), has been identified as a mechanically transmitted potexvirus (Alphaflexiviridae). In Argentina, cassava is grown mainly in the northeast (NEA) region that shares borders with Brazil and Paraguay. Increasing incidences of CCMD were observed during the years 2014 to 2016 associated with severe leaf mosaic symptoms and yield reductions where the occurrence of CsCMV was confirmed by RT-PCR and sequencing. In this work, the virus has been successfully purified and a double-antibody sandwich (DAS-) ELISA test has been developed from an Argentinean isolate of CsCMV to extend the diagnostics of the disease. A collection of 726 samples was screened and CsCMV was detected with 100% prevalence in the NEA region. Additional co-infecting viruses were detected in some plants (64.4%); in these, CCMD symptoms correlated with CsCMV only, although more severe symptoms could be observed in mixed infected plants. Sequence analysis of the conserved RdRp domain showed a wider diversity of CsCMV isolates. Interestingly, a separate phylogenetic cluster was formed by isolates from the NEA region that only shared 77.1% to 80.3% nucleotide identity with the other clusters. These results indicate the presence of mixed strains occurring in the NEA region and suggest the presence of geographically distinct strains of CsCMV in South America.